Technology Training of Teachers to Work in Science Classes of Physical and Mathematical Profile (Pedagogy of Higher and Secondary Education, 2012)
Fedorchuk A.L. Technology Training of Teachers to Work in Science Classes of Physical and Mathematical Profile.The article deals with the peculiarities of preparation of future teachers science to work in specialized classes. Technology of preparing future professionals to work in school physics and mathematics account.
Keywords: training future teachers; teacher preparedness science; technology teacher training